88.6k views
0 votes
Rearrange Equation to have y alone.

10x-2y=46

2 Answers

2 votes

Answer:

y= 5x-23

Explanation:

10x-2y =46

10x-10x-2y =46-10x

-2y= 46-10x

-2y/-2= 46-10x/-2

y= 5x-23

User Gabriel Sosa
by
5.1k points
5 votes

Answer:

y = 5x - 23

Explanation:

Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, subtract 10x from both sides:

10x (-10x) - 2y = 46 (-10x)

-2y = -10x + 46

Next, divide -2 from all terms in the equation:

(-2y)/-2 = (-10x + 46)/-2

y = (-10x)/-2 + (46)/-2

y = 5x - 23

y = 5x - 23 is your answer.

~

User Amit On
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.